The POLST paradigm and form:Facts and analysis. (1st May 2013) - Brugger, Christian; Breschi, Louis C.; Hart, Edith Mary; Kummer, Mark; Lane, John I.; Morrow, Peter T.; Smith, Franklin L.; Toffler, William L.; Beffel, Marisa; Brehany, John F.; Buscher, Sara; Marker, Rita L.
Abstract : This white paper, prepared by a working group of the Catholic Medical Association, provides a commentary on a new type of end-of-life document called a POLST form (Physician Orders for Life-Sustaining Treatment) as well as on its model (or "paradigm") for implementation across the United States. After an introductory section reviewing the origin, goals, and standard defenses of the POLST paradigm and form, the paper offers a critical analysis of POLST, including an analysis of the risks that POLST poses to sound clinical and ethical decision-making. The paper ends with several recommendations to help Catholic healthcare professionals and institutions better address the challenges of end-of-life care with alternatives to POLST.